The Educational Needs of English Language Teachers in the Basic Education Stage In Homs Governorate from the specialized teachers point of view - معروف سعاد; إسماعيل إسماعيل محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims at identifying The Educational Needs of English Language Teachers in the Basic Education Stage in Homs Governorate, and thedifferences between the average scores of the rspodents of the research sample on the questionnaire of educational needs of English language teacgers in the basic education stage in Homs governorante according to variables: ( gender, educational qualification, number of years of experience, number of training sesssions) . The current research was based on the descriptive and analytical approach. The research tool consisted of a questionnaire that the researcher prepared and studies psychometrically, and consisted of (444) male and female teachers, with a representation rate (45.49%) from the original community, and the research reached the following results: 1. There is no statistically significant differences between the average scores of the respondents of the research sample on the questionnaire of educational needs of English language teachers according to the variable of gender. 2.There are statistically significant differences between the average scores of the respondents of the research sample on the questionnaire of the educational needs of English language teachers according to the educational qualification variable for the benefit of teachers who do not an educational qualification . 3. There are statistically significant differences between the average scores of the respondents of the research sample on the questionnaire of the educational needs of English language teachers according to the number of years of experience variable in favor of teachers who have years of experience ( 5 years or less ) There are statistically significant differences between the averagescores of the respondents of the research sample on the questionnaire of the educational needs of English language teachers according to the variable number of trainging courses in favour of ( two courses or less)